2013
DOI: 10.2807/ese.18.23.20497-en
|View full text |Cite
|
Sign up to set email alerts
|

Legionnaires’ disease in Italy: results of the epidemiological surveillance from 2000 to 2011

Abstract: Binary file ES_Abstracts_Final_ECDC.txt matches

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 22 publications
(26 reference statements)
5
29
0
Order By: Relevance
“…Such improvement has already been reported in Italy over the 2000−11 period [15]. In other countries with stable ASR, the increasing number of LD cases would be compatible with an effect of demographic change with increasing numbers of at-risk older people.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Such improvement has already been reported in Italy over the 2000−11 period [15]. In other countries with stable ASR, the increasing number of LD cases would be compatible with an effect of demographic change with increasing numbers of at-risk older people.…”
Section: Discussionsupporting
confidence: 65%
“…This has been documented in Italy where a study has suggested higher under-reporting in central and southern regions compared with northern regions [15]. This analysis could not capture such heterogeneity, but these findings could be highly valuable for informing national policies.…”
Section: Discussionmentioning
confidence: 96%
“…Contrastingly, no shift was observed with hyperthermia, which is in line with its ineffectiveness at reducing Legionella colonization. The continuous injection of chlorine-based biocides evidently selects the most resistant Legionella spp., in our experience L. pneumophila serogroup 1, which is also the most virulent (1). In order to support this hypothesis, other authors reported the persistence of serogroup 1 in hospital water systems despite the adoption of chlorine-based disinfection strategies (53,54).…”
Section: Discussionsupporting
confidence: 64%
“…he number of cases of Legionnaires' disease has increased steadily over the years, especially in Italy and Europe (1,2). In 2013 in Italy, most cases were community acquired (83.4%), followed by travel-associated (9.8%) and health care-associated (4.6%) (3) cases.…”
mentioning
confidence: 99%
“…Improved surveillance has been noted as a potential reason for the continued increase of legionellosis incidence across Europe [19,36]. The Australian Department of Health has documented a sharp increase in reported legionellosis cases, from 122 to 382, between 1991 and 2012 [6].…”
Section: Discussionmentioning
confidence: 99%